PENGEMBANGAN PERANGKAT PEMBELAJARAN BERDASARKAN MODEL EXPERIENTIAL LEARNING PADA MATERI LINGKARAN KELAS VIII SMP/MTs - Adnan, Mustika Aulia; Suanto, Elfis; Zuhri, Zuhri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research was conducted due to the importance of learning instruments as the lesson plans which is arranged by teacher in order to achieve to learning goals. The available of learning instruments is limited, and does not refer 2013’s Curriculum yet. The purpose of this research is to develop the mathematics learning instrument: syllabus, lesson plans (RPP), and student worksheets (LKPD) using the experiential learning model on circle subject for 8th grade students that is categorized as valid and the LKPD is categorized as practical. This research used Research and Development (R&D) model with ADDIE procedure; analyze, design, development, implementation, and evaluation. The research instruments that used in this research were learning instruments validation sheets and student response questionnaires. Syllabus, RPP, and LKPD validated by 3 validator and revised according to suggestion from validator. The valid LKPD then tested in two stages, the small group trial and large group trial. According to the result of validation data analysis of learning instruments, those were categorized as very valid with the average score for syllabus was 4.56, for RPP was 4.61, and LKPD was 4.58. According to the result of student response questionnaires the LKPD was practical with the percentage reaches 90.84% in large group trials. According to the result of data analysis and the discussion, it can be concluded that the learning instruments using the experiential learning model on circle subject were very valid, and the LKPD were very practical to be used by 8th grade students of junior high school.Key Words: Experiential Learning Model, Mathematics Learning Instrument, Circle.